Uji Efektivitas Gel Ekstrak Etanol Daun Binahong (Anredera cordifolia) Sebagai Penyembuhan Luka Pada Tikus Wistar Jantan (Rattus norvegicus) - Siregar, Mardiana; Huda, Nurul; Afika, Ariyati N; Aida, Nur; Syahfitri, Siska; Anglia, Rima; Budyana, Irenia Putri (Jurnal Farmasi & Sains Indonesia, 2025)
The ethanol extract of binahong leaves contains alkaloids, flavonoids, steroids, tannins and saponins. The compounds contained in the extract have an important role in healing skin incision. The aim of this study was to develop a gel formula for binahong leaf extract (Anredera cordifolia (Ten.) Steenis) with various HPMC gelling agents at concentrations of 2%, 3% and 4%. This study is an experimental study by comparing the effectiveness of incision wound healing in rats in each test group, namely negative control given gel base, positive control given Bioplacenton gel, and the gel formulation of binahong leaf with best stability properties of the gel preparation. The best formula for binahong leaf extract gel is with a concentration of 2% HPMC with consideration of evaluating the physical properties of the gel and the fastest healing effect on burns.